Psychology in Malaysia: current trends and future directions - Abdul Rahman, Shukran (Pearson, 2012)
The objective of this paper is to discuss the current trends and contributions of psychology in Malaysia as well as the roles of psychology in raising the quality of life in Malaysia. The suggestions of the way forward for the field of psychology in Malaysia are also discussed, the goals being to provide a direction for this field to practise and studies in Malaysia. The following section discusses the current scenario in Malaysia that necessitates the contribution of psychology, followed by the current trends on the roles of psychology in the country.